Evaluation of Water Vapor Permeability of Cloth: Praewa Silk and Diamondtextile - Ongwuttiwat, Krittiya (Princess of Naradhiwas University Journal, 2019)
This research has valuated water vapor permeability ofPraewa Silk and Diamond Textile. Which is to Toinvestigate and compare water vapor permeability of Praewa Silk and Diamond Textile with toreference textiles. Knitted Polyester is permeable, while coated Nylon-Spandex is semi-permeable. Testing cup contained with warm water, dataloggers and mounted with different textile. cupTheywere weighted. Air temperature and relative humidity under and above the textile were recorded to find water vapor transfer rate, water vapor pressure difference varied on time. The results indicate that Praewa Silk and Diamond Textile have lower water vapor permeability than knitted Polyester but higher than coated Nylon-Spandex. The water vapor permeability of Praewa Silk and Diamond Textile are 12.56 x 10-9kg/m2•s•Pa and 10-9kg/m2•s•Pa, respectively.These results can be used to predict the thermal comfort in term of heat loss due to water vapor diffusion.